Experimental and simulation assessment of an adaptable cooling coil in the tropics. (1st April 2023) - Ning, Baisong; Sekhar, Chandra; Schiavon, Stefano; Tham, Kwok Wai; Cheong, David; Jia, Hongyuan; Anand, Prashant
Abstract: Overcooling or too high humidity issues may occur when the cooling coil in the central air-conditioning system is inadequate to meet both room temperature and humidity requirements, which might affect indoor thermal comfort, air quality, and building energy efficiency. Developing more advanced cooling coils to adapt to cooling load changes is one of the promising solutions to overcome these issues. This paper presents both experimental and detailed simulation results for an "adaptable coil", in which the coil row number is changed based on the building cooling load. Theoretically, when fewer rows are activated at part-load conditions, the coil's effective heat transfer area is reduced, which enables the coil surface temperature to be lower; hence the coil dehumidification performance can be improved. Actually, from our experimental study on a small-sized coil, we found that the adaptable coil shows an average 0.8% relative humidity reduction, while its water flow rate is more stable than a conventional coil. We also conducted detailed EnergyPlus simulations for a typical large-sized building in Singapore and found that the adaptable coil shows about 2.8% of relative humidity reduction and negligible overcooling reduction. Moreover, the adaptable coil shows better performance in reducing overcooling and space humidity, when the coil is heavily oversized and a large minimum airflow fraction is set. In summary, the adaptable coil does not show significant humidity and overcooling reduction advantages for a properly sized and well-operated air-conditioning system. Though with operational flexibility, the benefits of the adaptable coil are not as promising as expected; nevertheless, these results and conclusions may be valuable for future studies focusing on similar solutions for overcooling and high humidity issues. Graphical abstract: Image 1 Highlights: We performed both experimental and detailed simulation studies on adaptable cooling coil. Adaptable coil shows a 0.8% relative humidity reduction based on the experimental results. Adaptable coil shows about 2.8% relative humidity reduction based on the simulation results. Adaptable coil does not show promising advantages in reducing overcooling and high humidity issues. Adaptable coil might be beneficial in oversized and not well-operated variable air volume systems.